A mathematical model of mechanical properties influenced by manganese in DH36 high-strength ship plate steel - WU Jian-zhong; SHI Xiao; GUO Han-jie; GUO Jing (工程科学学报)
Plate products of DH36 high-strength ship plate steel,roll formed by a steelworks in China,were investigated. Analyzing by mathematical simulation method,a mathematical model was built for the connection between main chemical components and basic mechanical properties of DH36 high-strength ship plate steel. Based on the model,the impact of composition fluctuation of manganese on various mechanical properties was emphatically analyzed. The results show that the influence of manganese on impact energy mainly appears as the negative linear relationship. The impact of manganese on the yield strength,tensile strength and reduction of area also appears as the linear relationship,and the slope is impacted by other elements and needs further investigation.